Integrated Analysis of Cytoskeleton-Associated lncRNAs and Their Regulatory Networks in Mouse Oocyte Maturation - Suresh V Chinni; Genliang Li; Lin Luping (Malaysian Journal of Science (MJS), 2025)
With the increase in maternal age and the impact of environmental stress, the decline in ovarian reserve and oocyte quality has emerged as a primary cause of infertility. Dysfunction of cytoskeletal proteins plays a central role in this process. This study aims to examine the differential expression and regulatory functions of cytoskeleton-associated long non-coding RNAs (lncRNAs) during the development of mouse oocytes at the germinal vesicle (GV) and metaphase II (MII) stages. This study employed bioinformatics analyses and machine learning techniques to analyze publicly accessible data from the Gene Expression Omnibus (GEO) database, which comprised 13 samples of Germinal Vesicle (GV) stage oocytes and 15 samples of Metaphase II (MII) stage oocytes. Differential expression analysis, weighted gene co-expression network analysis (WGCNA), and interaction network construction were performed to screen for lncRNAs closely related to oocyte development. A total of 338 differentially expressed lncRNAs (DE-lncRNAs) with statistical significance were identified, including 136 upregulated and 202 downregulated lncRNAs, indicating their potential roles in the transition from the GV to the MII stage during oocyte development. WGCNA further identified modules strongly correlated with cytoskeletal proteins by integrating these results with the differentially expressed lncRNAs. A total of 47 candidate lncRNAs were shortlisted. Subsequently, LASSO regression and random forest algorithms were applied to identify six key lncRNAs from the candidate set. Combined with miRNA prediction and target gene analysis, a lncRNA-miRNA-mRNA regulatory network was constructed, revealing that these key lncRNAs may indirectly regulate downstream target gene expression through specific miRNAs. Furthermore, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses indicated that these key lncRNAs are primarily involved in cytoskeletal remodeling, cell proliferation, and differentiation, and may play critical roles in follicle structure formation and oocyte development. This study systematically mapped the regulatory network of lncRNAs during oocyte development and elucidated the lncRNA-miRNA-mRNA interactions. The results emphasize the key roles of lncRNAs in cytoskeletal remodeling and oocyte maturation, providing valuable insights for the diagnosis and treatment of ovarian disorders.